Abortion and the politics of motherhood - Luker, Kristin (University of California Press, 1984)
This study of the abortion controversy in the United States argues that moral positions on abortion are intimately tied to views on sexual behaviour, the care of children, family life, technology, and the importance of the individual.
Includes index.
Keywords: Right to Life Movement; Umschulungswerkstätten für Siedler und Auswanderer -- Bitterfeld; Abortion -- United States.; Abortion -- Political aspects -- United States.; Pro-life movement -- United States.; Motherhood -- Moral and ethical aspects.; Politics, Practical.; Abortion.; Attitude (Psychology); Fetus.; Individuality.; Women's rights.; Abortion, Therapeutic.; Civil rights.; Contraception.; Cultural pluralism.; History.; Labor (Obstetrics); Mothers.; Physicians.; Pregnancy.; Pregnant women.; Social values.; Motherhood -- Moral and ethical aspects -- United States.; Politics; Abortion, Induced; Attitude; Beginning of Human Life; Fetus; Individuality; Life; Personhood; Public Policy; Women's Rights; Abortion, Legal; Abortion, Illegal.; Abortion, Therapeutic; Civil Rights; Contraception; Cultural Diversity; Embryo, Mammalian; Family Relations; History; Jurisprudence; Labor, Obstetric; Moral Obligations; Mothers; Physicians; Pregnancy; Pregnant People.; Sexuality; Social Responsibility; Social Values; United States; Motherhood -- United States -- Moral and ethical aspects.; Avortement -- États-Unis.; Avortement -- Aspect politique -- États-Unis.; Maternité -- Aspect moral -- États-Unis.; Mouvement pour le respect de la vie -- États-Unis.; Maternité -- Aspect moral.; Politique.; Avortement.; Attitude (Psychologie); Fœtus.; Individualité.; Femmes -- Droits.; Avortement thérapeutique.; Droits de l'homme.; Diversité culturelle.; Histoire.; Travail (Obstétrique); Mères.; Médecins.; Grossesse.; Femmes enceintes.; Valeurs sociales.; politics.; civil rights.; history (discipline); mothers.; physicians.; pregnancy.; SOCIAL SCIENCE -- Abortion & Birth Control.; SOCIAL SCIENCE -- Gender Studies.; Women's rights; Social values; Pregnant women; Politics, Practical; Cultural pluralism; Civil rights; Abortion; Abortion -- Political aspects; Motherhood -- Moral and ethical aspects; Pro-life movement; Mutterschaft; Schwangerschaftsabbruch; USA; Abortus provocatus.; Moederschap.; Sociale bewegingen.